PENGARUH PENERAPAN WORK FROM HOME (WFH) DAN STUDY FROM HOME (SFH) TERHADAP AKTIVITAS BELAJAR MENGAJAR MATA KULIAH TEORI - Purba, Jhon Hericson; Andayani, Nur Rahmah (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2021)
The purpose of this study is to determine the implementation and measure the level of teaching and learning activities during the implementation of WFH and SFH. The case studied is theory courses at Politeknik Negeri Batam. The implementation of work from home (WFH) and study from home (SFH) is a learning method that is carried out when there is an urgent situation, namely the outbreak of Covid-19 virus in the world. The research was conducted using a descriptive analysis method with a percentage. The data were collected using observation sheets, questionnaires, and analyzed using a Likert scale. The results of the observations stated from 15 lecturers shows that 99.77% of lecturers carried out indirect online learning and 0.333% of them carried out direct online learning. The sample of this study is 120 students who were taken randomly from all of Politeknik Negeri Batam students taking general education as the population. The results of the hypothesis testing using SPSS stated that there is a positive effect of the implementation of WFH and SFH on teaching and learning activities by 43.9% and the t test results in a significant value of 0.00 <0.05 from the real level. The results of the tcount (9,610) > t table (1.986) so it can be concluded that H0 is rejected and Ha is accepted, that there is a positive effect of the application of WFH and SFH on teaching and learning activities with the indicators of teaching and learning activities for the WFH and SFH method being Achievement, Critical thinking, Communication Interaction, Teaching Role, and Evaluation system.